Effects of Dietary Protein Levels on Growth Performance, Carcass Traits, Serum Metabolites, and Meat Composition of Tibetan Sheep during the Cold Season on the Qinghai-Tibetan Plateau - Xungang Wang; Tianwei Xu; Xiaoling Zhang; Yuanyue Geng; Shengping Kang; Shixiao Xu (Animals, 2020)
Dietary protein is a critical nutrient that directly influences the health and production of livestock. Recent studies showed that protein supplements could enhance the growth performance of Tibetan sheep. However, there is a lack of information regarding the influence of dietary protein levels on carcass traits and meat composition. This study investigated the effects of dietary protein levels on growth performance, carcass traits, serum metabolites, and meat composition in Tibetan sheep during the cold season on the Qinghai-Tibetan Plateau. A total of eighteen 1-year-old, healthy, castrated Tibetan sheep with similar initial body weights (31.7 ± 0.72 kg) were randomly divided into three treatment groups with different dietary protein level (low protein (LP, 10.1%); medium protein (MP, 12.1%); high protein (HP, 14.1%)) diets. The results indicated that the Tibetan sheep fed with the MP and HP diets had greater final body weights (BWs), average daily gains (ADGs), and average daily feed intakes (ADFIs) (p < 0.05). The MP and HP diets also improved the hot carcass weight, net meat (including the fat) weight, and bone weight of the sheep significantly (p < 0.05). Besides, the dietary protein levels could significantly affect the serum concentrations of growth hormone (p < 0.05). The diameter of muscle fibers in the MP group was significantly greater than that in the LP group (p < 0.05), while the density of muscle fibers showed the opposite trend. The dietary protein levels only significantly (p < 0.05) influenced the ether extract content and profile content of the longissimus dorsi muscle but had no effect on other parameters of meat composition. In summary, our results indicate that dietary protein levels affect growth performance, carcass traits, and meat composition and that diets containing 12.1% and 14.1% protein are recommended to obtain better production performance and meat products in Tibetan sheep, rather than a diet containing 10.1% protein, during the cold season on the Qinghai-Tibetan Plateau.